Food systems practitioner and education resource database - Kaley Hohenshell; Courtney Long (Urban Food Systems Symposium, 2022)
This report shares insights from The Food Systems Practitioner and Education Resource Database that was created in 2021 through a cooperative agreement with USDA Agricultural Marketing Service (AMS) in partnership with nine different organizations as a second phase of the Food Systems Core Competency project. The database aims to highlight and bring awareness to partner networks, educational resources, and food systems practitioners. It serves as an identification tool for individual to find mentors, peers, and learning opportunities related to personal and professional growth desires. This paper will review the database and its potential uses, profile types and network engagement opportunities.
Keywords: competencies; framework; community; food systems; leadership